A Bibliometric Analysis of Internal Audit Research in Indonesia - Firdausi, Qonita; Safitri, Sari; Manulang, Novrianti; Dachlan, Fitriana; Santoso, Rachmat Agus (Golden Ratio of Finance Management, 2025)
This research aims to describe the evolution of internal audit, focusing on identifying the most productive and cited articles, authors, countries, and institutions on this topic. The study used bibliometric analysis with VOSviewer software based on Scopus data, covering 490 articles published from 2017–2023. Data was collected using the "internal audit" keyword and analyzed to identify publication trends, author collaborations, and citation patterns. The results showed that the number of publications on internal audits continues to increase, with 2020 being the most productive year, with 80 articles (16.33%). The United States leads in the number of articles and citations, followed by Malaysia and other countries. Authors such as Eulerich Marc and institutions such as Brigham Young University are among the most productive in this study. The article " Influence of Audit Committee and Internal Audit Function Effectiveness on Enterprise Risk Management Adoption" by Callahan et al. is the most cited. The implications of this study show the importance of the evolution of the role of internal audit in risk management, control, and organizational governance, especially in the era of digitalization. Then, for further research evolution, other software and visualization methods can be used besides VOSviewers, such as CiteSpace or Gephi, to provide more comprehensive insights into the structure of internal audit research.